ANALISIS IMPLEMENTASI PROGRAM POS PEMBINAAN TERPADU PENYAKIT TIDAK MENULAR (POSBINDU PTM) DI KECAMATAN BANGUNTAPAN KABUPATEN BANTUL - Lutfy Laksita Pranandari; Septo Pawelas Arso; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2017)
Banguntapan is the highest number of program target of Posbindu PTM in Bantul, that is 82.728 people. The coverage of PTM Posbindu activities is 0.52% including the red category (less than 10%) and the proportion of measurement of abdominal circumference by 60% including the red category. The objective of this research was analyze implementation of Posbindu PTM program in Banguntapan District, Bantul Regency. The type of research is qualitative descriptive with in-depth interview and observation. The research informants were head of kader, target of Posbindu PTM, programmer staff of infectious diseases, head of primary healthcare center, and staff of controlling infectious diseases sub unit mental health in Semarang District Health Office. The result of the research show that the implementation of Posbindu PTM program in Banguntapan sub-district has not been optimal yet because it has not been routinely done yet, the partnership still had limited, the implementation of the service stage still has not optimum in interview stage, measurement, examination and identification of PTM risk factors and counseling. It was influenced by communication, resources, disposition, and  bureaucracy structure. In communication to the target and cross-sector was still lacking, the kader  were not understand the calculation of IMT. In resources, from the aspect of human resources the number of cadres has not been sufficient and the facilities of the provision of inspection strips were not sufficient. In disposition, response, commitment, and motivation of the implementer was good, but the commitment of primary healthcare center in assistance less. In the variable of bureaucracy structure, organizational structure has not been written yet, decree formation of Posbindu PTM had not been made, job division still has not optimum in service of PTM risk factor identification and counseling, and supervision have not done optimally. Suggestions from this research were socialization to the target, establishing partnership, refr8eshing kader about IMT, making decree, and monitoring of periodic evaluation.